The macrophage marker translocator protein (TSPO) is down-regulated on pro-inflammatory 'M1' human macrophages - Narayan, N; Mandhair, H; Smyth, E; Dakin, S; Kiriakidis, S; Wells, L; Owen, D; Sabokbar, A; Taylor, P (Plubic Library of Science, 2017)
The translocator protein (TSPO) is a mitochondrial membrane protein, of as yet uncertain function. Its purported high expression on activated macrophages, has lent utility to TSPO targeted molecular imaging in the form of positron emission tomography (PET), as a means to detect and quantify inflammation in vivo. However, existing literature regarding TSPO expression on human activated macrophages is lacking, mostly deriving from brain tissue studies, including studies of brain malignancy, and inflammatory diseases such as multiple sclerosis. Here, we utilized three human sources of monocyte derived macrophages (MDM), from THP-1 monocytes, healthy peripheral blood monocytes and synovial fluid monocytes from patients with rheumatoid arthritis, to undertake a detailed investigation of TSPO expression in activated macrophages. In this work, we demonstrate a consistent down-regulation of TSPO mRNA and protein in macrophages activated to a pro-inflammatory, or 'M1' phenotype. Conversely, stimulation of macrophages to an M2 phenotype with IL-4, dexamethasone or TGF-β1 did not alter TSPO expression, regardless of MDM source. The reasons for this are uncertain, but our study findings add some supporting evidence for recent investigations concluding that TSPO may be involved in negative regulation of inflammatory responses in macrophages.